Production of bioactive compounds by Aspergillus kept under two preservation conditions - Prado, Fabiano Brito; Rocha, Waldireny Caldas; Martim, Salomão Rocha; Alecrim, Mircella Marialva; Silva, Larissa de Paiva; Silva, Larissa Svetlana Cavalcante; Silva, Taciana de Amorim; Teixeira, Maria Francisca Simas (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
In order to verify the influence of the preservation method on the activity of secondary metabolites and to select species of Aspergillus as sources of compounds with antimicrobial activity, this study was made with Aspergillus from the DPUA collection of cultures. The strains were reactivated, and their viability was confirmed based on morphological characteristics and reproductive structures. The production of the biocompounds was made in YES agar. The ethanolic, ethyl acetate, and hexane organic extracts were tested by the agar well diffusion method against Staphylococcus aureus, Escherichia coli and Candida albicans. The extracts that presented antibiosis in this test were analyzed by immersion bioautography and were determined at minimum inhibitory concentrations by broth microdilution method. The method of preservation in distilled water promoted greater stability and purity of the Aspergillus cultures, independent of storage time, compared to the method of preservation in mineral oil, especially in relation to the phenomenon of pleomorphism. The data presented here showed that Aspergillus species, although preserved for different periods under in vitro conditions, synthesize compounds with antibacterial and antifungal activity to inhibit the growth of S. aureus, E. coli and C. albicans.